(untitled) (Studia Prawnicze / The Legal Studies, 2008)
Zagadnienie szkolnej nauki religii wzbudzało w Polsce poważne społeczne kontrowersje szczególnie w pierwszej połowie lat dziewięćdziesiątych XX w. Wprowadzenie nauczania religii do przedszkoli oraz szkół publicznych w drodze instrukcji Ministra Edukacji Narodowej (MEN) z dnia 3 oraz 24 sierpnia 1990 r. przez wielu oceniane było jako sprzeczne ze świeckim charakterem oświaty gwarantowanym przez ustawę z 1961 r. o rozwoju systemu oświaty i wychowania, zasadą świeckiego charakteru państwa oraz jego neutralnością światopoglądową, wreszcie jako kolidujące z konstytucyjną wówczas zasadą rozdziału Kościoła od państwa. Trybunał Konstytucyjny w kontrowersyjnym orzeczeniu z 30 stycznia 1991 r. (sygn. akt K.11/90) legitymizował jednak działania MEN. Optional religious education at school in Poland is first of all regulated by the decree of the Minister of National Education of 14th April , 1992 on the conditions and methods of the organizationof religious education in public kindergartens and schools. In 1993, the Constitutional Tribun aI, at the request of the Ombudsman, examined some of the decisions of this decree and found them consistent with the constitution. Presently, however, after passing the constitution in 1997 and after ratifying the concordat in 1998, there are different control patterns. Also, different provisions ofthe decree of 1992 are the subject ofanalysis. This document does not speciĄl clearly who is to collect the declaration of will to learn religion or ethics. We do not know how long such a declaration is valid. This violates the principle of determinateness of law. Also, the limit of 7 interested persons in a class (group) obliging a school to organize lessons ofreligion or ethics is contrary to the constitution. This limit is not based by the law, it violates the principle of equal rights for religious associations and their constitutional right to teach religion at school. Also, as far as Catholic children are concerned, it is inconsistent with the concordat. The principles of employing religion teachers seem to be contrary to the constitution as well. The decree of 1992 violates the constitutional principle of the closed system of the sources of the generally binding law. The fact that only Christian pupils can be given free time from school to participate in the Lent Retreat is contrary to the principle of equal rights for religions. The possibility of placing the cross in a classroom violates the principle of state neutrality toward religion. It is inconsistent with the constitutional principle of impartiality of public administration with regard to religious, ideological and philosophical beliefs. Summing up, there are grounds for appealing against the decree of 14th April, 1992 to the Constitutional Tribunal.